2023
DOI: 10.3917/rsss.021.0007
|View full text |Cite
|
Sign up to set email alerts
|

Après l’effort… que devient le corps ? Ruptures et continuités corporelles chez les ex-sportif•ve•s de haut niveau

Abstract: Si les représentations et pratiques corporelles des sportif·ve·s de haut niveau sont bien connues, on ignore encore largement ce qu’elles deviennent lors de l’après-carrière. Reposant sur une enquête auprès de 30 ex-sportif•ve•s de haut niveau, cet article propose de décrire, au travers de trois portraits, les processus de socialisation constitutifs de rapports au corps spécifiques. Les résultats montrent que les rapports au corps de ces individus peuvent être rapportés, pour partie au moins, à l’articulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The injunctions of the athlete's entourage concerning body weight control can also lead to the embodiment of body self-surveillance, and even to eating disorders that can last well beyond the sports career (McMahon & Penney, 2013). Some studies have shown that family socialization can be more or less congruent with sports socialization (Rasera, 2016), and that the latter more often represents transformative or conversion socialization for working-class athletes, while it is more akin to reinforcement socialization for those from middle-and upper-class backgrounds (Longchamp et al, 2023) 2 .…”
Section: High-level Sport and Body Socializationmentioning
confidence: 99%
“…The injunctions of the athlete's entourage concerning body weight control can also lead to the embodiment of body self-surveillance, and even to eating disorders that can last well beyond the sports career (McMahon & Penney, 2013). Some studies have shown that family socialization can be more or less congruent with sports socialization (Rasera, 2016), and that the latter more often represents transformative or conversion socialization for working-class athletes, while it is more akin to reinforcement socialization for those from middle-and upper-class backgrounds (Longchamp et al, 2023) 2 .…”
Section: High-level Sport and Body Socializationmentioning
confidence: 99%